Descriptions of two new species of Zeyanus Huber (Hymenoptera: Mymaridae), with notes on some other congeneric taxa from the oriental part of China. (3rd April 2017) - Triapitsyn, Serguei V.; Aishan, Zhulidezi; Hu, Hong-ying
Abstract: Two new species of Zeyanus Huber (Hymenoptera: Mymaridae), Zeyanus kweishuilini Triapitsynsp. n. and Zeyanus shihi Triapitsynsp. n., are described from Taiwan, China. Taxonomic notes and illustrations are also provided for Zeyanus asulcifrons (Zeya) and Zeyanus sergueii (Manickavasagam & Rameshkumar), both newly recorded from the Oriental part of China. An updated key to all described, valid species of Zeyanus is given. Also reported is the first known host for an unidentified member of the genus from Thailand, a Ledra sp. (Hemiptera: Cicadellidae: Ledrinae). http://zoobank.org/urn:lsid:zoobank.org:act:931EDFAE-19FF-4C64-AAEE-3563E62D8C68 http://zoobank.org/urn:lsid:zoobank.org:act:55D9EE6E-1CB1-43B8-97B2-E8AF631D42BA